Analisis Pandangan Masyarakat Terhadap Adanya Asuransi Takaful Keluarga - Yuni Winda (Al-Sharf: Jurnal Ekonomi Islam, 2022)
Sharia insurance is an investment to face future risks come. The purpose of this research to see the responses or views of community to familly takaful insurance. The succes of the sharia insurance company cannot escape the role of society in the importance of insurance. But on the other hand still many people do not know about the existence of family takaful insurance. As for field research, literature and interviews.